Role of School Leadership and Institutional Support in Promoting ICT Use Among Teachers - Shil, Dhiman; Gupta, S. K. (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Information and Communication Technology (ICT) is key in assisting in improving teaching and learning outcomes at the era of the digital transformation in education. While the success of integration of ICT to school contexts largely depends on the schools leadership and the level of institutional support offered to teachers. This paper investigates the contribution of school leadership as well as institutional frameworks in promoting ICT adoption among teachers. The paper draws on empirical studies and on theoretical frameworks to document key factors that affect ICT integration such as visionary leadership, creation of collaborative cultures, infrastructure, and initiatives in building capacity. Therefore, as a conclusive note, the study states that in order to have sustainable ICT driven educational innovation, school leaders should be empowered as well as institutional support mechanisms should be strengthened.